2005
DOI: 10.1021/jf050439g
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Flavor Release from French Fries Using Atmospheric Pressure Chemical Ionization−Mass Spectrometry

Abstract: Flavor release from French fries was measured with atmospheric pressure chemical ionization-mass spectrometry (APCI-MS) using both assessors (in vivo) and a mouth model system (in vitro). Several volatiles measured with APCI were identified with MS-MS. The effect of frying time, salt addition, and an alternative process using superheated steam was determined on I(max) (maximum intensity of compounds) and on t(max) (time of maximum intensity). In vitro a "chewing" frequency of 0.60 Hz caused an increased t(max)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Zehentbauer et al (2000) showed that humidity leads to an enhancement of the signal intensity. The detection of flavors in the mouth cavity after swallowing food was possible with APCI-MS as well (Van Loon et al, 2005). Taylor and Linforth (2003) compared APCI with ESI and showed the ability of APCI to ionize also compounds of low volatility (e.g., glucose, sucrose and citric acid).…”
Section: Atmospheric Pressure Chemical Ionizationmentioning
confidence: 99%
“…Zehentbauer et al (2000) showed that humidity leads to an enhancement of the signal intensity. The detection of flavors in the mouth cavity after swallowing food was possible with APCI-MS as well (Van Loon et al, 2005). Taylor and Linforth (2003) compared APCI with ESI and showed the ability of APCI to ionize also compounds of low volatility (e.g., glucose, sucrose and citric acid).…”
Section: Atmospheric Pressure Chemical Ionizationmentioning
confidence: 99%
“…In the field of food science, both methods have been largely applied for food product characterization, traceability and/or classification . More and more studies benefit from their time resolution and sensitivity to perform on‐line analysis, either for process monitoring or for nose‐space analysis while a food product is consumed .…”
Section: Introductionmentioning
confidence: 99%
“…The experimental determination of the aroma compound concentrations in the nasal cavity is now possible due to sufficiently sensitive and fast in vivo volatile measurement techniques such as atmospheric pressure chemical ionization (APCI-MS) or proton transfer reaction (PTR-MS) coupled with mass spectrometry. In the recent years, in vivo studies of volatile release using APCI-MS (e.g., Hodgson et al 2004;Van Loon et al 2005;Bayarri et al 2006;King et al 2006; or PTR-MS (Hansson et al 2003;Aprea et al 2006;Boland et al 2006) became more and more abundant. But the data For permissions, please e-mail: journals.permissions@oxfordjournals.org processing is often limited to computation of maximum intensities, slopes, areas, durations, and relative comparisons between these descriptors and if possible with sensory properties.…”
Section: Introductionmentioning
confidence: 99%